Melkersson-rosenthal syndrome associated with hemifacial spasm - Komurcu, Hatice Ferhan; Anlar, Omer (International Journal of Research in Medical Sciences, 2017)
Melkersson-Rosenthal Syndrome, with findings of repeating facial paralysis, orofacial edema, and fissured tongue, is rarely seen clinically. We present the case of a 49-year-old female patient diagnosed with Melkersson-Rosenthal Syndrome, with the association of hemifacial spasm. The case diagnosed as Melkersson-Rosenthal Syndrome by the symptoms of the recurrent episodes of facial paralysis, labial edema, and lingual fissure, accompanied by hemifacial spasm is the first to be reported in the literature.